The Role of Economic and Political Factors in Shaping Consumers' Confidence in Pakistan (Journal of Social Sciences Review, 2023)
Consumer confidence is an important determinant of economic growth. However, consumer confidence itself is determined by the economic and political situation of the country. This paper contributes to the literature by examining the role of economic and political factors in developing consumer confidence in Pakistan over the period from February 2012 to December 2020. Economic factors include GDP growth, inflation, interest rate, stock returns and exchange rate while elections, terror attacks and news are taken as political factors affecting Consumer confidence. Regression analysis is performed and models are estimated using the OLS.  The results show that economic variables such as inflation and economic growth are statistically significant determinants of consumer confidence in Pakistan. However, when political variables are added to the model, the explanatory power of the model significantly increases. Political variables such as elections and terror attacks have a statistically significant impact on the confidence of Pakistani consumers. The findings of this paper imply that consumer confidence is an important determinant of economic well-being and business cycle fluctuations of a country itself determined by economic and political factors where political factors play a dominant role in Pakistan.
Keywords: Consumer Confidence; uncertainty; Economic factors; Political factors; Elections; Terror attacks